(3ebGdI aj Cf cd eJUd jfbSe Edi CTjGA jfbSe OGFekG HZjQ fgGjIs - (3GHf YOj , jMji Hf YOj Hf MejO Hf RcQjG, CHh RcQjG,J (B364 (3g` s
(3ChdgG (B:s
(3GdGTjGA GdeJJGdjI gi GdJi dGJhLO ajgG TF eeG jONd ai fhYgG hPdc Gfg djS eGfY ef Gf jchf ajeG Hjf GdeJJGdjI TF BNQ s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3djJ TYQi JRja bhd GbdjOS Gf GdNW jfbSe fUajf hHGbi GdGbSGe hCf jJQcH s
(3Vef eLehY , JQJjHgG (B: (3GdNGeS YTQs
(3GfXQg eY GdeNWhW Qbe (B302 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B211s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdadSaI hGdefWbs